Analisis Faktor-Faktor yang Mempengaruhi Kepercayaan Konsumen Serta Implikasinya Terhadap Keputusan Pembelian (Studi kasus pada Go-Ride di Kota Bandung) - Hakim, Reza Haikal; Idris, Idris (Faculty of Economics and Business Diponegoro University, 2017)
This research is aim to analyze the influence of service quality and perceived usefulness against purchase decision through consumer trust in Go-Ride services especially in Bandung. Service quality and perceived usefulness become distinctive reason for consumer in using Go-Ride as an effective means of transportation. The population used in this research is Go-Ride service user in Bandung. This research method is using a non-probability sampling technique by purposive sampling method which the samples used were 151 respondents. Data obtained from the questionnaire which are processed and analyzed using SEM (Structural Equation Modeling) through AMOS program. The results showed that Service Quality and Perceived Usefulness have positive and significant impact on Consumer Trust. Subsequently the Consumer Trust has positive and significant impact on the Purchase Decision. In addition, both of independent variables also have a positive and significant impact on the Purchase Decision Go-Ride services in Bandung.